Novel insights: crosstalk with non-puerperal mastitis and immunity - Zhou, Yao; Gong, Jie; Deng, Xianguang; Shen, Lele; Liu, Lifang (Frontiers in Immunology, 2024)
The two primary types of non-puerperal mastitis (NPM) are granulomatous lobular mastitis (GLM) and plasma cell mastitis (PCM). Existing research indicates that immune inflammatory response is considered to be the core of the pathogenesis of GLM and PCM, and both innate and adaptive immune responses play an important role in the pathophysiology of PCM and GLM. However, the regulatory balance between various immune cells in these diseases is still unclear. Consequently, we present a comprehensive summary of the immune-related variables and recent advances in GLM and PCM.